Case report: An unusual case of cecal mucosal bleeding. Issue 1 (9th December 2022) - Kamara, Maseray S.; Sugawa, Choichi
Abstract: Cecal mucosal bleeding is an undocumented and rare cause of lower gastrointestinal (GI) bleeding. We present a case of a 73‐year‐old woman with end‐stage renal disease and paroxysmal atrial fibrillation on apixaban who presented with lower gastrointestinal bleed. She was found to have symptomatic, acute chronic anemia requiring multiple packed red blood cell transfusions. Colonoscopy revealed a localized area of active, cecal mucosal bleeding without evidence of Dieulafoy lesion, ulcer, mass, arteriovenous malformation, or diverticula. Hemostasis was achieved with epinephrine injection and the use of bipolar electrocautery. She was later resumed on her therapeutic anticoagulation without recurrence of bleeding. Therapeutic anticoagulation in our patient with ESRD increased her risk for gastrointestinal bleeding. Had this transient, mucosal‐limited bleeding not been active during endoscopic evaluation, the etiology of her massive gastrointestinal bleeding would have been missed. This case expands the differential of acute, lower GI bleeding to include cecal mucosal bleeding, which is a rare, intermittent, cause of bleeding that is amenable to endoscopic management.